Improvement of fluconazole flowability and its effect on dissolution from tablets and capsules - Vladi Olga Consiglieri; Samanta Mourão; Mauricio Sampaio; Patricia Granizo; Pedro Garcia; Valeska Martinello; Rodrigo Spricigo; Humberto Gomes Ferraz (Universidade de São Paulo, 2010)
The aim of this work was to improve fluconazole flowability by wet granulation and to study the effect of granulation on drug dissolution from tablets and capsules. Fluconazole was submitted to a process of wet granulation in a high-speed granulator using Plasdone® K29/32 or K90. Flow properties of granules and dissolution profiles for tablets and capsules produced with them were determined. Fluconazole granules demonstrated better flowability, calculated by angle of repose and compressibility index data, compared with powder. Additionally, it was observed that the granulation process improved the dissolution efficiency (ED) of fluconazole from tablets and capsules, which could also suggest an increase in bioavailability. Higher dissolution efficiencies were achieved with Plasdone® K29/32. O objetivo deste trabalho foi melhorar as características de fluxo do fluconazol com o emprego da granulação úmida e estudar o efeito desse processo na dissolução do fármaco em cápsulas e comprimidos. O fluconazol foi submetido ao processo de granulação úmida num granulador de alta velocidade empregando Plasdone K29/32 e K90. Foram determinadas as propriedades de fluxo dos grânulos e obtidos os perfis de dissolução de cápsulas e comprimidos obtidos com os granulados em estudo. Os grânulos de fluconazol apresentaram melhores características de fluxo após o processamento, demonstradas por meio das determinações do ângulo de repouso e do índice de compressibilidade, comparativamente à matéria-prima. Adicionalmente, observou-se que o processo de granulação melhorou a eficiência de dissolução (ED) do fluconazol nos comprimidos e cápsulas.